Simulasi Pengendalian Kualitas Pengaruh Deformasi Material Condenser Tube terhadap Proses Tube Expanding Waterbox Condenser (Studi Kasus di PT. BBI Pasuruan) - Pratama, Aditya Wahyu; Wahyudi, Slamet; Santoso, Purnomo Budi (Rekayasa Mesin, 2014)
Leakage tube after tube expanding process is still occurred in PT. BBI Pasuruan due to imperfect material deformation. Material deformation cause by a change in material form due to external forces such as temperature, friction force, compressive force, and the torque style. Deform 3D was used in this investigation to determine the material deformation processes. Taguchi method design of experiment was also used to minimize the bad cause of the poor performance is also influenced by several variables or factors on the characteristics of the desired quality. The results shows that the combination to prevent deformation of the material in the condenser tube are the friction between the tool and the tube expander of 0.787 inch, the material used is stainless steel ASTM A 249 grade 2, tube expanding process temperature optimum of 89.6 F, and expander velocity of 0.708 inches per second.Keywords: Taguchi method, design of experiment, tube expanding, material deformation